A prospective decision-impact study incorporating Breast Cancer Index into extended endocrine therapy decision-making. (5th March 2019) - Sanft, Tara; Berkowitz, Alyssa; Schroeder, Brock; Hatzis, Christos; Schnabel, Catherine A; Brufsky, Adam; Gustavsen, Gary; Pusztai, Lajos; Londen, GJ van
Aim: To prospectively assess the impact of gene expression-based assay Breast Cancer Index (BCI) on extended endocrine therapy (EET) decision-making.Patients & methods:  The BCI-tested samples from primary tumors (Stage I–III, hormone receptor positive breast cancer, >3.5 year endocrine therapy). Patients and physicians completed questionnaires on EET preferences and decision conflict. Using these data, a fact-based economic model was developed to project the cost impact of BCI.Results:  The BCI results affected treatment recommendations for 42/141 patients (overall mean, 62 year; 83% postmenopausal; 63% Stage I). Patient decision conflict decreased pre- to post-test. The BCI-related projected net savings (US$5190/patient) was robust under sensitivity analysis.Conclusion: Incorporating BCI into clinical practice meaningfully impacted physician EET recommendations and decreased patient decision conflict, with projected cost savings.